A heart afire : stories and teachings of the early Hasidic masters - Schachter-Shalomi, Zalman, 1924-2014.; Miles-Yepez, Netanel (Philadelphia : Jewish Publication Society, 2009)
A guided tour of Hasidism and Hasidic storytelling introducing the reader to rare and unique translations of Hasidism. Gives readers the opportunity to immerse themselves in the world of Hasidic wisdom and narrative and in the teachings of a modern Hasidic teacer.
The hidden tradition and the Ba'al Shem Tov -- The circle of the Ba'al Shem and the Maggid of Mezritch -- The circle of the Maggid and the rebbe king.
Includes bibliographical references (pages 383-390) and index.
Translated from the Hebrew.
Print version record.
Master record variable field(s) change: 650
Keywords: Hasidim -- Legends; Rabbis -- Legends; Jewish legends; Hasidism -- History; Hasidim -- Legends; Hasidism -- History; Jewish legends; Rabbis -- Legends; RELIGION -- Judaism -- General; Hasidim; Hasidism; Jewish legends; Rabbis; Chassidismus; Electronic books; History; Legends; Electronic books